A Novel Prothrombotic Pathway in Systemic Sclerosis Patients: Possible Role of Bisphosphonate-Activated γδ T Cells - Marcu-Malina, Victoria; Balbir-Gurman, Alexandra; Dardik, Rima; Braun-Moscovici, Yolanda; Segel, Michael J.; Bank, Ilan (Frontiers in Immunology, 2014)
Abstract: Objectives: Infusions of aminobisphonates (ABP) activate Vγ9δ2T cells in vivo, and induce an acute inflammatory response in 30% of patients treated for osteoporosis. Following the observation of digital thrombosis in a patient with systemic sclerosis (SSc) who was treated with an intravenous ABP, zoledronate (Zol) we evaluated whether patient and control PB mononuclear cell (MC, PBMC) acquire a pro-thrombotic phenotype in response to zoledronate (Zol). Results: Vγ9δ2T cells, of both patients and healthy donors (HD), upregulated the CD69 activation antigen and secreted tumor necrosis factor (TNF)α in response to Zol in vitro. In addition, exposure to either Zol or lipopolysaccharide (LPS), or to both additively, induced expression of the highly procoagulant, tissue factor (TF)-1 on CD14+ monocytes. Importantly, only Zol-induced TF-1 was blocked by a monoclonal antibody to TNFα. Interestingly, we found that SSc but not healthy donor (HD) Vδ1+ T cells, were concurrently activated by Zol, to produce interleukin (IL)-4. Plasma of the SSc patient who developed critical digital ischemia after infusion of Zol, but neither plasma from a second patient who had no adverse clinical response to Zol infusion nor of a HD, strongly enhanced Zol induced monocyte TF-1, which could still be blocked by anti-TNFα. Conclusions: ABP induced secretion of TNFα by Vγ9δ2+T cells may lead to TNFα dependent induction of pro-coagulant TF-1 induction, on monocytes. In certain clinical settings, e.g. SSc, TF-1+monocytes could play a role in triggering clinically relevant thrombosis.